Predictors of meaningful improvement in quality of life after temporal lobe epilepsy surgery: A prospective study. (23rd March 2017) - Pauli, Carla; Schwarzbold, Marcelo Liborio; Diaz, Alexandre Paim; de Oliveira Thais, Maria Emilia Rodrigues; Kondageski, Charles; Linhares, Marcelo Neves; Guarnieri, Ricardo; de Lemos Zingano, Bianca; Ben, Juliana; Nunes, Jean Costa; Markowitsch, Hans Joachim; Wolf, Peter; et al.
Summary: Objectives: To investigate prospectively the independent predictors of a minimum clinically important change (MCIC) in quality of life (QOL) after anterior temporal lobectomy (ATL) for drug‐resistant mesial temporal lobe epilepsy related to hippocampal sclerosis (MTLE‐HS) in Brazilian patients. Methods: Multiple binary logistic regression analysis was performed to identify the clinical, demographic, radiologic, and electrophysiologic variables independently associated with MCIC in the Quality of Life in Epilepsy‐31 Inventory (QOLIE‐31) overall score 1 year after ATL in 77 consecutive patients with unilateral MTLE‐HS. Results: The overall QOLIE‐31 score and all its subscale scores increased significantly (p < 0.0001) 1 year after ATL. In the final logistic regression model, absence of presurgical diagnosis of depression (adjusted odds ratio [OR] 4.4, 95% confidence interval [CI] 1.1–16.1, p = 0.02) and a complete postoperative seizure control (adjusted OR 4.1, 95% CI 1.2–14.5, p = 0.03) were independently associated with improvement equal to or greater than the MCIC in QOL after ATL. The overall model accuracy for MCIC improvement in the QOL was 85.6%, with a 95.2% of sensitivity and 46.7% of specificity. Significance: These results in Brazilian patients reinforce the external validation of previous findings in Canadian patients showing that presurgical depression and complete seizure control after surgery are independent predictors for meaningful improvement in QOL after ATL, and have implications for the surgical management of MTLE patients.